Pengaruh Media Pop Up Book dalam Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Sinaga, Hermanson; Damanik, Noni Epitasari; Hutabarat, Morentina; Sihaloho, Elvayani; Haloho, Tri Anggi Karunia; Siahaan, Windi Yovita; Purba, Yoel Octobe (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study aims to examine the effect of the Pop-Up Book media in improving students’ mathematics learning outcomes, particularly on the topic of plane geometry, in Grade II of UPTD SD Negeri 124397 Pematangsiantar. The primary issue underlying this research was the low level of students’ enthusiasm and conceptual understanding, which was attributed to the use of monotonous instructional methods. The lack of student engagement resulted in suboptimal learning outcomes, as students experienced difficulty in visualizing abstract mathematical concepts. The research employed a descriptive quantitative approach to provide a systematic overview of the impact of the instructional media on students’ learning abilities. Data were collected through observations of classroom learning activities and documentation of students’ test results. The data were then analyzed quantitatively by comparing students’ performance between conventional teaching methods and interactive media-based instruction, in order to measure the extent to which the learning media variable contributed to improving students’ understanding of plane geometry concepts. The findings indicate that the use of the Pop-Up Book media has a positive and significant effect on improving students’ learning outcomes. This media effectively transforms abstract plane geometry material into engaging three-dimensional (3D) visual representations, thereby creating a more enjoyable and interactive learning environment for students